Charitable Habituation as Transformational Character Education: Forming Students' Islamic Character - Yasukma Amanda; Sapri (Al-Qalam Institute, 2026)
Character education in madrasahs frequently remains ceremonial, leaving a persistent gap between the regular delivery of religious activities and their internalisation in students' daily conduct. This study examines the implementation of the Gerakan Amal Sholeh (GAS, or Righteous Deeds Movement) at MTsN 2 Deli Serdang, with the aim of understanding how the program is organised, how it contributes to the formation of students' Islamic character, and what factors support and hinder its implementation. Employing a descriptive qualitative method with a phenomenological approach, data were gathered through in-depth interviews, participant observation, and documentation involving the principal, the vice principal for curriculum, teachers, the student organisation chairperson, and students, and were analysed using the interactive model of Miles and Huberman with source and methodological triangulation. The findings reveal that the program operates as an integrated system in which transparent habituation of infaq, teacher role modelling (uswah hasanah), and the genuine delegation of responsibility move students gradually from external compliance toward the internalisation of sincerity, trustworthiness, social awareness, and discipline, with charitable habits extending beyond the madrasah into the home. Its principal implication lies in reconceptualising charitable habituation as a form of transformational education and learning, in which routine moral practice becomes the mechanism for a durable transformation of disposition, motivation, and moral agency, offering educators a replicable model for cultivating Islamic character through transparently designed and authentically modelled philanthropic practice.